PERLINDUNGAN HUKUM TERHADAP ANAK ANGKAT - Atin Meriati Isnaini (Jurnal Ilmu Hukum Tambun Bungai, 2017)
The adoption of a child is a legal act which diverts a child from the sphere of parental authority, legal guardian, or other person responsible for the care, education and rearing of the child, into the host family environment. The adoption of children has been regulated by the Government Regulation No. 54 of 2007 on the Implementation of the Rapture. In Government Regulation No. 54 of 2007 has been determined in detail, strict and strict about the procedures and conditions of adoption of children. It is intended that the implementation of adoption in accordance with the purpose of the child so that the child gets the welfare, both education, health, and life in the future. The achievement of the main goal of adoption is one of the concrete efforts of the Government to provide legal protection for adopted children.